VILLAGE LEVEL ENERGY UTILIZATION OF COPRA PRODUCTION BY PRODUCTS IN EASTERN VISAYAS, PHILIPPINES - Engr. Eutiquio E. Sudaria (International Coconut Community Journal, 1989)
Coconut is one of the important crops of the farmers in Eastern Visayas. Forty‑two percent of the agricultural land of Eastern Visayas is planted to coconut. Coconut farmers are earning money mainly from the main product of coconut which is copra. The price of copra is fluctuating. Hence, there is a need for the farmers to utilize the by‑products of copra production to augment their income. The by‑products depend on the copra making practice of the farmers. For the direct splitting method where the nut with husk is split directly with an axe, combined husk with shell locally known as "binuongan" or "bukong" and water are the by‑products while the husking method has the byproducts of separate husk, shell, and water. This paper covers only the utilization of the "binuongan", husk and shell. The water is excluded. Paper also describes the utilization of copra making by‑products practiced by farmers and developed at the Regional Coconut Research Center, VISCA, Baybay, Leyte.